Stabilizing Unequal Positions in Copyright Licensing Agreements in Book Publishing: Comparison of Approach between the European Union and Indonesia - Angga Priancha; Annisa Elda; Aurizza Amanda; Bambang, Fardy Laksana; Sihombing, Regina (PADJADJARAN LAW RESEARCH AND DEBATE SOCIETY, 2024)
Book publishing involves licensing agreements between authors and publishers, often leading to inequitable compensation due to imbalanced bargaining power. This research employs doctrinal legal methodology to analyze and compare copyright licensing norms in both the EU and Indonesia. The EU Directive on Copyright in the Digital Single Market (“EU CDSM Directives”) prioritizes enhancing copyright protections and enforcing party rights among member states, particularly emphasizing authors' rights to renegotiate contracts under specific conditions. It is proposed that Indonesia should adopt guidelines that prioritize authors' interests in licensing contracts, acknowledging their disadvantaged bargaining position. Implementing such measures through regulations like Presidential Decrees could streamline processes, thus benefiting authors. Additionally, Indonesia should tailor EU CDSM Directives to local contexts, ensuring enhanced protection and fairer contracts for authors.